SP0005 Risk factors for osteoarthritis. (1st June 2001) - Doherty, M
Abstract : Osteoarthritis (OA) is not a disease or a single condition. Diverse observations suggest that it may reflect the repair process of synovial joints. Sites commonly targeted by symptomatic OA include finger joints, knees and hips. These sites have different risk factors for development of structural OA. Different risk factors may relate to structural progression and outcome. Risk factors for pain and disability (such as muscle weakness and adverse psychosocial factors for the knee) may also differ from those relating to structural change. Risk factors for development of structural OA are divisible into general constitutional factors and local, predominantly biomechanical factors. Important constitutional factors include heredity and ageing (all sites); Caucasian ethnicity (hip); female gender (hands, knees); and obesity (knees). Overt trauma can predispose to OA, but so may specific repetitive activities relating to occupational and recreational usage (eg football, knee bending while load carrying – knee OA; farming – hip OA). Possible negative associations include osteoporosis (hip >knee) and smoking (knee >hip). The role of poor nutrition (especially low antioxidants and vitamin D) in development and progression of knee and hip OA merits further study. The genetic study of OA promises important insights into pathogenesis. A strong genetic contribution to OA of the hand, knee and hip has been shown using strategies such as: classic twin study; estimation of the relative risk of OA in siblings of OA patients; and segregation analysis of clustering of OA within families. Through candidate and genome wide association studies of affected sibling pairs, genetic associations are now being identified on several chromosomes (notably 2q, 11 and 16) and it is hoped that predisposing genes will shortly be identified. Inheritance is likely to be polygenic and to involve common polymorphisms, each with a relatively low attribution to OA. The next stage will be gene-gene and gene-environmental interaction studies to determine how individual genes and constitutional or environmental factors interrelate to cause OA and to modify its progress.